Realistic mathematics education: Mathematical reasoning and communication skills in rural contexts - Anderson Leonardo Palinussa; Juliana Selvina Molle; Magy Gaspersz (International Journal of Evaluation and Research in Education (IJERE), 2021)
Mathematics learning has always been a problem in the world of education in Indonesia especially in the Province of Maluku, which is a thousand island area. The geographical position of Maluku, which is an area of the archipelago, is quite extensive, affecting the quality of students in mathematics. One approach that is recommended to overcome mathematical problems of rural island-based students is realistic mathematics education (RME). The purpose of this study was to analyze the effect of RME on mathematical reasoning and communication skills in a rural context. The research design used was quasi experiment. The sample size was 130 students from several junior high schools in Central Maluku Regency. The instrument developed was in the form of problem descriptions to measure students' mathematical reasoning and communication skills. The findings prove that RME has a significant influence on students' mathematical reasoning and communication skills. Thus, RME can be recommended in improving students' mathematical reasoning and communication skills in the island-based rural context.